Diluwang Ponorogo Narrative As Enrichment Of Materials In Historical Learning Based On Local Wisdom - Itama Citra Dewi Kurnia Wahyu; Warto Warto; Leo Agung S (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
History learning generally refers to the material in the textbook and does not mention the local history that is around students. As a result, students are less interested and do not understand the historical material presented by the teacher. Lack of knowledge about local history in history learning material has an impact on the fading of the local values of students. The purpose of this study was to identify the use of Dluwang Ponorogo narrative as material enrichment in local wisdom-based historical learning. The method used in this research is qualitative research with data collection techniques in the form of literature studies. The findings of this study resulted in the conclusion that the use of local history in enriching history learning materials can increase the locality of learners. The enrichment of material in historical learning based on local wisdom can be obtained by students by studying the local history of the area where they live. In fact, local history is shaped by the local wisdom of the community and local wisdom itself comes from the culture of a community.